JEMBATAN SURAMADU ANTARA KONFLIK DAN DEHUMANISASI MASYARAKAT MADURA - M. Ali Al-Humaidy, M. Ali Al-Humaidy (Institut Agama Islam Negeri Madura)
Abstrac This simple artcile is not about to provoke Madurese people to deny the industrialization as the impact of Madura bridge establishment. However, theoretically the presence of industry causes social impact. The social conflict and dehumanisation (including marginalization and impoverishment) will be immediately occured if the industrialization process does not involve the role of the stakeholders entirely and consistantly. Suramadu bridge is built in attempt to increase Madurese economic potency. As a matter of fact, the bridge appears the symbol of the victory of global capitalism to exploit the maximum benefit of Madura potency. Kata-kata kunci Karl Marx, conflict, Industry